2020
DOI: 10.1002/hipo.23278
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional modulation of hippocampal and amygdala synaptic plasticity by post‐weaning obesogenic diet intake in male rats: Influence of the duration of diet exposure

Abstract: Obesity is a chronic condition associated with adverse memory and emotional outcomes in humans and animal models. We have recently demonstrated that postweaning (i.e., periadolescent) high-fat diet (HFD)-induced obesity has opposite effect on hippocampal and amygdala-dependent memory in rodents: while HFD consumption impairs spatial and relational memory, it enhances cue-dependent emotional memory. However, it is still not clear whether this bidirectional HFD effect on memory is related to bidirectional altera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In HPC, HFD effect is more pronounced in ventral CA1 and subiculum, which represent the main output of the vHPC (Britt et al, 2012; Cenquizca and Swanson, 2007; Ciocchi et al, 2015; Gergues et al, 2020; Liu and Carter, 2018). This could be related to HFD-induced morphological and electrophysiological changes in CA1 as it was reported that 8-12 weeks of post-weaning HFD intake enhances dendritic spine density in CA1 pyramidal neurons (Valladolid-Acebes et al, 2013) and induces aberrant in vivo long-term potentiation in CA1 (Vouimba et al, 2021). Thanks to our intersectional virus approach, we were able to restrict our c-Fos analyses to NAc-projecting or mPFC-projecting vHPC neurons located in ventral CA1/subiculum.…”
Section: Discussionmentioning
confidence: 93%
“…In HPC, HFD effect is more pronounced in ventral CA1 and subiculum, which represent the main output of the vHPC (Britt et al, 2012; Cenquizca and Swanson, 2007; Ciocchi et al, 2015; Gergues et al, 2020; Liu and Carter, 2018). This could be related to HFD-induced morphological and electrophysiological changes in CA1 as it was reported that 8-12 weeks of post-weaning HFD intake enhances dendritic spine density in CA1 pyramidal neurons (Valladolid-Acebes et al, 2013) and induces aberrant in vivo long-term potentiation in CA1 (Vouimba et al, 2021). Thanks to our intersectional virus approach, we were able to restrict our c-Fos analyses to NAc-projecting or mPFC-projecting vHPC neurons located in ventral CA1/subiculum.…”
Section: Discussionmentioning
confidence: 93%
“…In HPC, HFD effect is more pronounced in ventral CA1 and subiculum, which represent the main output of the vHPC ( Britt et al, 2012 ; Cenquizca and Swanson, 2007 ; Ciocchi et al, 2015 ; Gergues et al, 2020 ; Liu and Carter, 2018 ). This could be related to HFD-induced morphological and electrophysiological changes in CA1 as it was reported that 8–12 weeks of post-weaning HFD intake enhances dendritic spine density in CA1 pyramidal neurons ( Valladolid-Acebes et al, 2013 ) and induces aberrant in vivo long-term potentiation in CA1 ( Vouimba et al, 2021 ). Thanks to our intersectional virus approach, we were able to restrict our c-Fos analyses to NAc- or mPFC-projecting vHPC neurons located in ventral CA1/subiculum.…”
Section: Discussionmentioning
confidence: 93%
“…These results look contradictory to ours but can be explained by the length of HFS exposure, very short-term in the Valladolid-Acebes’ report and very long-term in Karimi’s experiment. Indeed, when 2-3 months HFS diet duration was compared to 6-7 months in the same study, LTP was found increased and decreased respectively [12]. Also of great interest for our study, thyroid hormones were reported to regulate the pattern of astrocytes maturation in cerebellum through THRα1 [50] and to up-regulate GLAST and GLT-1 in order to protect astrocytes and neurons against glutamate toxicity [51].…”
Section: Discussionmentioning
confidence: 96%
“…Importantly, we found that HFS diet impaired hippocampal-dependent memories when started in juveniles, but did not affect memory when started at adulthood [8], through aberrant activity of the hippocampus [10,11]. Specifically, such memory impairments have been found to be associated with higher c-fos expression in the hippocampus and hippocampal efferent pathways to striatal and prefrontal areas [10,11] as well as aberrant synaptic transmission and plasticity in CA1 [12]. Interestingly, chemogenetic manipulation of the hippocampus or its efferent pathways rescued memory deficits for object location and long-term object recognition [11,13].…”
Section: Introductionmentioning
confidence: 99%